High frequency communication and sensing traveling-wave techniques - Tekin, Ahmet; Emira, Ahmed (Devices, circuits, and systems, 2015)
This book introduces multiple patent-pending high-frequency traveling-wave signal generation and utilization circuit techniques. The aforementioned techniques offer a new vision for the architecture of many high-speed communication circuits. In addition to high-speed communication, these ideas are uniquely applicable to THz image sensing technologies. Recently, there has been a great deal of effort and research to reach THz frequencies using standard silicon-based fabrication technologies. This text presents some novel techniques to achieve this goal